The effects of increasing dietary methionine in the phase II starter pig diet - Owen, K.Q.; Kats, L.J.; Friesen, K.G.; Richert, B.T.; Musser, R.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 216 pigs (initially 12.4 lb and 21 d of age) was used in a 28 d growth trial to determine the effects of increasing dieatary methionine in the phase II ( d 7 to 28 postweaning) diet. Pigs were allotted by sex, weight, and ancestry and placed in pens containing six pigs each. All pigs were offered a common phase I diet for the first 7 d postweaning. The phase I diet contained 20% dried whey, 10% spray-dried porcine plasma (SDPP), 3% lactose, and 1.75% spray-dried blood meal (SDBM) and was formulated to contain 1.6% lysine and .44% methionine. After the phase I period, pigs were assigned to one of six treatments that contained either .27, .30, .33, .36, .39, or .42% dietary methionine. Methionine levels were obtained by adding increasing levels of DL-methionine to a common basal diet. The control diet was corn-soybean meal-based, contained 10% dried whey and 3% SDBM, and was formulated to contain 1.3% lysine and .27% methionine. During phase I (d 0 to 7 postweaning), average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) were .68 lb, .67 lb, and 1.01, respectively. During the first week of phase II (d 7 to 14 postweaning), increasing dietary methionine resulted in improved ADG, ADFI, and F/G. For the cumulative period (d 7 to 28 postweaning), ADG and ADFI were not influenced by increasing dietary methionine; however, F/G was improved and appeared to be maximized at .36% methionine. These data suggest that the early-weaned pig requires .36% dietary methionine during d 7 to 28 postweaning to maximize growth performance when fed a diet containing 1.3% lysine. Also, when expressed relative to lysine, this represents a methionine:lysine ratio of 28%. This corresponds to the same methionine to lysine ratio found to optimize performance during the phase I trial.
Keywords: Swine; Methionine; Starter pigs; Performance